1983
DOI: 10.1097/00000658-198309000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Incompatible Kidney Survival in Outbred Higher Primates without Chronic Immunosuppression

Abstract: Transplantation between non-identical humans has been limited by the requirement for chronic immunosuppression (CI). This study demonstrates in a nonhuman primate model that long-term acceptance of incompatible kidney allografts can be achieved without the use of CI. Following incompatible kidney transplantation, rhesus monkey recipients were given a 5-day course of clinical rabbit antithymocyte globulin (RATG). On day 12, unfractionated donor bone marrow (BM) was infused intravenously. Recipients were monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Thomas et al observed that kidney transplanted rhesus macaques receiving 50 mg/kg of rATG for 5 days followed by a single infusion of unfractionated donor bone marrow on day 12 experienced longterm survival past 248 days without evidence of graft versus host disease, infection, or rejection (compared to 35.8 days for rATG alone, p , 0.001); a second donor bone marrow infusion on day 24 reversed the benefit, however, as the animals rejected with a mean graft survival time of 76.6 days (Thomas et al 1983). In revisiting the ATG þ dBM model, the group observed a reduced median survival of 70 days, still a considerable feat in the absence of chronic immunosuppression (Thomas et al 1989).…”
Section: Polyclonal Antibody Preparationsmentioning
confidence: 99%
“…Thomas et al observed that kidney transplanted rhesus macaques receiving 50 mg/kg of rATG for 5 days followed by a single infusion of unfractionated donor bone marrow on day 12 experienced longterm survival past 248 days without evidence of graft versus host disease, infection, or rejection (compared to 35.8 days for rATG alone, p , 0.001); a second donor bone marrow infusion on day 24 reversed the benefit, however, as the animals rejected with a mean graft survival time of 76.6 days (Thomas et al 1983). In revisiting the ATG þ dBM model, the group observed a reduced median survival of 70 days, still a considerable feat in the absence of chronic immunosuppression (Thomas et al 1989).…”
Section: Polyclonal Antibody Preparationsmentioning
confidence: 99%
“…Approximately a decade later, encouraged by Judy Thomas's work with the primate model, 14,15 Monaco performed three living-related kidney/bone marrow transplantations, using the same triple drug induction therapy (including ALG) and administration of 3 to 5 × 10 8 cryopreserved bone marrow cells/kg on postoperative day 21. 16 Two of the recipients did well, with no evidence of rejection at 11 and 13 months after transplantation, and had evidence of decreasing donor-specific responsiveness.…”
Section: The Monaco Modelmentioning
confidence: 99%
“…Tolerant mice showed evidence of low degree (up to 4%) chimerism (microchimerism) (3). Subsequent studies in mongrel dogs (4,5) and nonhuman primates (6,7) demonstrated that the use of polyclonal ALS and donor BMC is also very effective in producing tolerance to kidney allografts. Posttransplant donor BMC infusion with induction therapy by polyclonal antilymphocyte globulin was clinically applied in living-related and cadaveric kidney transplantation with a standard multidrug immunosuppressive protocol (8 -10).…”
mentioning
confidence: 99%